"Antioxidant activity and characterization of protein fractions and hydrolysates from normal and quality protein maize kernels". (July 2017) - Ortiz-Martinez, Margarita; Otero-Pappatheodorou, José T.; Serna-Saldívar, Sergio O.; García-Lara, Silverio
Abstract: Maize is the main crop cultivated worldwide with more than 1 billion metric tons produced annually and is one of the most relevant sources of protein for human consumption in developing countries. Proteins and peptides isolated from maize exert relevant antioxidant activity which is increased by enzymatic hydrolysis. However, there is limited information about the antioxidant potential of proteins isolated from Quality Protein Maize (QPM) varieties and their hydrolysates. The aim of this research was to determine the differences in protein profile and antioxidant activity of protein fractions and hydrolysates between a hybrid white maize (Asgrow 773) and a QPM variety (CML-502). The biophysical evaluation and the total protein quantification by Kjeldahl and fractions by ninhydrin were consistent with the changes due to the breeding process of the QPM material. The antioxidant potential of the hydrolysates obtained from albumins and globulins had a 3-fold increase in both maize varieties. The prolamins hydrolysates presented an increase of 7-fold for the normal variety and 2-fold for the QPM variety. The results of this research allow indicate that the QPM varieties are a source of antioxidant peptides and promising candidates in the search for proteins and peptides with other bioactivities. Highlights: Antioxidant activity of proteins and hydrolysates differ between varieties of maize. Proteins and hydrolysates from QPM present higher antioxidant potential. Improved varieties of maize are potential sources of antioxidants.